MENINGKATKAN MAHĀRAH KALĀM DENGAN ASSERTIVENESS TRAINING: STUDI KUASI-EKSPERIMENTAL DI MTSN 4 SURABAYA - Irawan, Yumna Nazih; Ali Wafa; Junaedi (Al-Katib: Jurnal Pendidikan Bahasa Arab, 2025)
Abstract This study aims to evaluate the effectiveness of assertive training in improving Arabic speaking skills (mahārah kalām) among students of MTsN 4 Surabaya. The research is grounded in the observation that many learners face psychological barriers such as shyness, low self-confidence, and fear of making mistakes when speaking Arabic. Assertive training was selected as the intervention because it emphasizes confidence-building, appropriate self-expression, and the courage to communicate without pressure. A quasi-experimental design with a non-equivalent control group was employed, involving an experimental group receiving assertive training and a control group using conventional instruction. Research instruments consisted of a speaking test and observational checklists assessing oral performance. The results reveal a significant improvement in the experimental group’s posttest scores compared to the control group, as demonstrated through a t-test with a p-value < 0.05. These findings indicate that assertive training effectively enhances students’ fluency, accuracy, and communicative confidence in speaking Arabic. Therefore, assertive training is recommended as an alternative pedagogical strategy for Arabic language instruction, particularly in strengthening communicative competence. Further research is suggested to expand variables related to affective factors and the integration of interactive digital media in communicative learning contexts.